PERSEPSI MASYARAKAT TENTANG TRADISI BERSIH DESA MELALUI KESENIAN WAYANG KULIT DI DESA O MANGUNHARJO KABUPATEN MUSIRAWAS - Wahyuni, Putri; Isbandiyah; Miyarni, Ira (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This study aims to determine the public perception of the implementation of the BersihDesa tradition through wayang kulit art in O Mangunharjo Village, Musi RawasRegency. The Bersih Desa tradition is a local cultural heritage that contains spiritual, social, and cultural values ​​that continue to be preserved by the community. Wayangkulit art is used as the main media in a series of Bersih Desa activities which are believed to be able to convey moral and religious messages to the community effectively. The research method used is a descriptive qualitative method with data collection techniques in the form of observation, in-depth interviews, and documentation. Informants in this study consisted of community leaders, wayang kulitartists, village officials, and residents involved in the tradition. The results of the study showed that the community has a positive perception of the Bersih Desa tradition through wayang kulit performances. The community considers this tradition not only as a form of entertainment, but also as a means of strengthening social relations, fostering a sense of gratitude, and maintaining harmony between humans and nature. In addition, wayang kulit art is considered to have an important role in maintaining local cultural identity and being an effective educational medium for the younger generation. Thus, the preservation of the Clean Village tradition through shadow puppetry needs to continue to be supported by various parties so that cultural values ​​and local wisdom are maintained amidst the current of modernization.